2005
DOI: 10.2337/diabetes.54.7.1907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fructose Overfeeding and Fish Oil Administration on Hepatic De Novo Lipogenesis and Insulin Sensitivity in Healthy Men

Abstract: High-fructose diet stimulates hepatic de novo lipogenesis (DNL) and causes hypertriglyceridemia and insulin resistance in rodents. Fructose-induced insulin resistance may be secondary to alterations of lipid metabolism. In contrast, fish oil supplementation decreases triglycerides and may improve insulin resistance. Therefore, we studied the effect of high-fructose diet and fish oil on DNL and VLDL triglycerides and their impact on insulin resistance. Seven normal men were studied on four occasions: after fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
254
4
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(284 citation statements)
references
References 39 publications
16
254
4
10
Order By: Relevance
“…32 It is likely that most humans are responders to sucrose/fructose overconsumption and that fish oil supplementation inhibits sucrose-induced fatty liver. With respect to HF dietinduced fatty liver, patients with fatty liver have been shown to consume significantly more saturated fat per day than control subjects matched for body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…32 It is likely that most humans are responders to sucrose/fructose overconsumption and that fish oil supplementation inhibits sucrose-induced fatty liver. With respect to HF dietinduced fatty liver, patients with fatty liver have been shown to consume significantly more saturated fat per day than control subjects matched for body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that increasing the fructose content of the diet increases plasma triglycerides, through several mechanisms, among which are a stimulation of hepatic de novo lipogenesis [26], and a decreased VLDL-triacylglycerol clearance [27]. Based on animal experiments, an increased VLDL-triacylglycerol secretion is also likely to be involved [28].…”
Section: What Are the Mechanisms Responsible For Fructose-induced Metmentioning
confidence: 99%
“…In humans, a high-fructose, hypercaloric diet leads to ectopic fat deposition in liver cells and skeletal muscle in humans already after a 1-wk period [31]. There is strong evidence that fructose decreases hepatic insulin sensitivity in humans [26,32,33], and that a 10-wk high-fructose diet impairs glucose homeostasis in overweight individuals [34]; however, few studies have directly evaluated the effect of a high-fructose diet on whole body insulin sensitivity. It has been reported that supplementation with various amounts of fructose for up to 4 wk failed to decrease whole body insulin sensitivity in healthy individuals [31,35].…”
Section: What Are the Mechanisms Responsible For Fructose-induced Metmentioning
confidence: 99%
“…
Feeding rats high fructose diet affects both glucose and lipid metabolism which result in a cluster of metabolic abnormalities such as glucose intolerance, hypertension, dyslipidaemia and reduced insulin action (1,2) .The aim of the present study was to evaluate the potential influence of sardine protein on biomarkers of oxidative stress and inflammation in high fructose diet-induced metabolic syndrome rat.Male Wistar rats (n = 26) weighing 200°0 g were divided to four groups of six rats each and fed 20% casein (Cas) or sardine protein (SP) with or without 64 % fructose (F) for 2 months. Plasma glucose, insulin, lipids, tumour necrosis factor-a and leptin levels were determined.
…”
mentioning
confidence: 99%
“…Feeding rats high fructose diet affects both glucose and lipid metabolism which result in a cluster of metabolic abnormalities such as glucose intolerance, hypertension, dyslipidaemia and reduced insulin action (1,2) .…”
mentioning
confidence: 99%